Surveying Strategies for Hard-to-Survey Populations: Lessons From the Native Hawaiian and Pacific Islander National Health Interview Survey. - Galinsky, Adena M.; Simile, Catherine; Zelaya, Carla E.; Norris, Tina; Panapasa, Sela V. (American Journal of Public Health, 2019)
Calls for remedies for the persistent scarcity of accurate, reliable, national, disaggregated health statistics on hard-to-survey populations are common, but solutions are rare. Survey strategies used in community and clinical studies of hard-to-survey populations often cannot be, and generally are not, implemented at the national level. This essay presents a set of approaches, for use in combination with traditional survey methods in large-scale surveys of these populations, to overcome challenges in 2 domains: sampling and motivating respondents to participate. The first approach consists of using the American Community Survey as a frame, and the second consists of implementing a multifaceted community engagement effort. We offer lessons learned from implementing these strategies in a national survey, some of which are relevant to all survey planners. We then present evidence of the quality of the resulting data set. If these approaches were used more widely, hard-to-survey populations could become more visible and accurately represented to those responsible for setting national priorities for health research and services.